Pointwise Multipliers on Spaces of Homogeneous Type in the Sense of Coifman and Weiss - Yanchang Han; Fanghui Liao; Zongguang Liu (Abstract and Applied Analysis)
By applying the remarkable orthonormal basis constructed recently by Ausher and Hytönen on spaces of homogeneous type in the sense of Coifman and Weiss, pointwise multipliers of inhomogeneous Besov and Triebel-Lizorkin spaces are obtained. We make no additional assumptions on the quasi-metric or the doubling measure. Hence, the results of this paper extend earlier related results to a more general setting.